REGARDING THE ROLE OF REGULATORY AND LEGAL SECURITY IN THE DEVELOPMENT OF ELECTRIC MOBILE OF TRANSPORT IN UKRAINE - SLIUSAREVA, Liudmyla; MATVIICHUK, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the regulatory and legal provision of electric vehicle transport in Ukraine. Defined and the concepts of "electric cars" and "electric vehicle transport" are demarcated, possible directions and components are defined achieving results. The essential characteristics of the concept of electric mobile transport have been clarified. The legislation of Ukraine’s state environmental focuses on modernization of production to reduce the negative impact on the environment and the introduction of a green procurement system was studied. A number of key challenges of regulatory and legal support in Ukraine are highlighted, which shows about the inconsistent and insufficient regulation of relations in the field of electric transport, which should be aimed at stimulating the development of production in Ukraine of electric vehicles, chargers, accessories for them, preferential import. With the help of a thorough analysis of modern requirements for electric vehicle transport, the article offers comprehensive recommendations for optimization and adaptation of traditional strategies at the legislative level regarding the issue of conditions and terms of validity of the grace period, which changed several times. It can be stated that the normative and legal support does not fully comply with the norms legislation of the European Union regarding the integration of environmental policy into transport policy. The solution to this the issue requires improvement of some provisions, in particular, stimulation of the development of public transport, including electric transport and the development of incentives to encourage the renewal of the car fleet by providing preference for cars that meet environmental standards. On the basis of the conducted research, it is possible to testify that during the development of development programs environmental transport should take into account the influence of globalization processes, namely such factors as the presence environmental problems, fluctuations in prices for traditional energy carriers, the opening of patents for electric cars, distribution technological innovations, access to the Internet and digitalization of society.